SPEECH LEVELS AMONG JAVANESE YOUNG GENERATIONS : A Study of the Use of Javanese Speech Levels by Teenagers in Temanggung Regency in Central Java - Iin Isrokha, - (2011)
This research is conducted to describe the use of Javanese speech levels by Javanese young generations in Temanggung, central Java. This research examines the speech levels used by Javanese young generations (JYG) in Temangggung in their daily conversations, the factors that potentially influenced the choice of speech levels by Javanese teenagers, and their attitudes toward the speech levels. This research employed a qualitative descriptive method through non-participant observation and focus group interview. The data from both research methods are classified and analyzed to investigate the kind of speech levels used by JYG, the factors that influence the choice of that speech levels, and the JYGs' attitudes toward speech levels. The result of the analysis shows that Ngoko (Low form) is the most widely used by JYG in their daily conversations. It is found that 53,99% of 526 utterances is dominated by Ngoko, while Krama (Higer form) and Krama Inggil (Highest form) did not appear at all. Meanwhile, Madya appears only once in all the conversations. It is also found that the respondents sometimes mixed between Javanese speech level Ngoko and Indonesian language (45,81%). Furthermore, it is found that genders of the speakers, genders of parents, and intimacy and kinship appeared to influence the JYGs' choice of the speech levels. Finally, with regard to the JYGs' attitudes toward Javanese speech levels, it shows that JYG have a positive response in maintaining the speech levels.